Implementasi Kebijakan Peraturan Bupati Nomor 23 Tahun 2021 Tentang Penerimaan Peserta Didik Baru pada SD Negeri 104231 Batang Kuis Kabupaten Deli Serdang di Era Pandemi Covid-19 - Iwan Sutomo; Nina Siti Salmaniah Siregar; Budi Hartono (Mahesa Research Center, 2023)
This study employs a qualitative approach with a case study as the research design. The focus of the case study is on how SDN 104231 Batang Kuis handles the Admission of New Students in the midst of the Covid-19 outbreak after the issuance of Regent Regulation No. 23 of 2021. Data collection is conducted through interviews, observations, and documentation. The findings indicate that 1) preparation for this policy is carried out through understanding, learning, and preparing implementation strategies in accordance with supporting factors, such as selecting a competent committee for Admission of New Students and implementing staff who are willing to learn from changes; 2) policy implementation has been carried out in accordance with existing policies and has become a new point for having a better system for Admission of New Students and services by integrating offline and online systems in the educational environment; and 3) there are supporting and inhibiting factors, such as the simplification of Admission of New Students activities and students being able to participate in online competitions, but also negative impacts, such as a decrease in parents' interest in enrolling their children in public elementary schools since the Covid-19 pandemic and the need for the development of infrastructure used.